In House Training Implementasi Kurikulum Merdeka di SMPN 1 Cisitu Kabupaten Sumedang melalui Pendekatan Komunikasi : - Diah Fatma Sjoraida; Aat Ruchiat Nugraha; Iriana Bakti (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
In House Training is one of the institution's communication actions in an effort to increase knowledge and strengthen the ability to act in an activity for the internal public (teachers). Education as an activity needs to receive new input to be able to produce student outcomes that are of quality, intelligence and character. To get these results, guidelines and references are needed that are scientifically and practically accountable, one of which is through curriculum content that is competitive for schools. The Merdeka Curriculum, which is a "pragmatic" curriculum in the sense of combining concepts/theoretical and implementation simultaneously and continuously, is a new method for some teachers in state schools. Therefore, activities are needed to strengthen understanding of the independent curriculum and its implementation for teachers and education staff at SMPN 1 Cisitu Sumedang. In House Training for the Implementation of the Merdeka Curriculum was attended by SMPN 1 Cisitu Teachers using a delivery method approach in the form of lectures, discussions and simulations of preparing lesson plans for subjects included in the independent curriculum. As for the results of this Community Service (PPM) activity, participants (teachers and school management) became more knowledgeable and understanding in the practice of an independent curriculum which is strengthened by communication science studies to produce quality students. The conclusion is that the combination of educational science and communication science in the learning process that implements the independent curriculum is very relevant, creative and interactive among teachers and students, especially at SMPN 1 Cisitu Sumedang.